Beliefs, Teaching Practice and Proposals for the Attention of Cultural Diversity: the Case of a Costa Rican Teaching and Three Nicaraguans Infants - Lilian Susana Ruiz-Guevara (Universidad Nacional, Costa Rica, 2010)
This article presents data from a research that studied a teacher belief regarding three Nicaraguan students. Specifically, presents findings related to teaching practice and its relation to diverse education proposals. It includes an analysis of four subcategories: daily dynamic of a teacher who works with infants of another culture, students' assessment in the classroom, discipline strategies to children, and diverse beliefs and proposals. The data shows that, in the classroom, the teacher does not demonstrate different treatment to Nicaraguan and Costa Rican children, suggesting that equal treatment is the strategy per se used by the teacher to solve the issue of cultural diversity in the classroom. On the other hand, discipline is assumed by the teacher with scolding criteria, using a loud tone of voice and aggressive vocabulary.